This article is the result of a professional master's thesis in Education and New Technologies. It presents the analysis of data from semi-structured interviews, carried out with directors, pedagogues and teachers working in the state education network in the city of Curitiba. The objective of the research was to investigate the appropriation and use of the Online Class Record (RCO), a computerized school record tool in order to identify and analyze the relationship established between the subjects of the school and the digital technology in question. The authors who supported the research were Vieira Pinto (2005); Feenberg (2013); Paro (2016); Freire (2000); Brandão; Dagnino; Novaes, (2004); Ferreira (2001). When analyzing the subjects' speeches, 5 categories emerged from the research data: Conception of technology; Preparation for appropriation and use of the Online Class Registration; Technological apparatus; Functionalities of the digital tool (RCO); Democracy or control of teaching work. In the research, evidence was found that indicate that the RCO can be at the same time a democratic or controlling management tool depending on the purpose and intention of those who use it. (Olhar de Professor, 2022)
This article is the result of a professional master's thesis in Education and New Technologies. It presents the analysis of data from semi-structured interviews, carried out with directors, pedagogues and teachers working in the state education network in the city of Curitiba. The objective of the research was to investigate the appropriation and use of the Online Class Record (RCO), a computerized school record tool in order to identify and analyze the relationship established between the subjects of the school and the digital technology in question. The authors who supported the research were Vieira Pinto (2005); Feenberg (2013); Paro (2016); Freire (2000); Brandão; Dagnino; Novaes, (2004); Ferreira (2001). When analyzing the subjects' speeches, 5 categories emerged from the research data: Conception of technology; Preparation for appropriation and use of the Online Class Registration; Technological apparatus; Functionalities of the digital tool (RCO); Democracy or control of teaching work. In the research, evidence was found that indicate that the RCO can be at the same time a democratic or controlling management tool depending on the purpose and intention of those who use it.
Keywords: Online Class Registration. Philosophy of Technology. Pedagogical work.